Migraine and tension-type headache: a few historical aspects - Cauás, Michelly; Lima, Murilo Costa; Lago, Carlos Augusto Pereira do; Ponzi, Elizabeth Arruda Carneiro; Oliveira, Daniella Araujo de; Valença, Marcelo Moraes (Headache Medicine, 2010)
The primary headaches are routinely present in today's society, among the main representatives are tension-type headache (TTH) and migraine. We reviewed a few historical aspects about primary headaches.